We have the equation 9x^2 + 4y^2 + 36x – 8y + 4 = 0

9x^2 + 4y^2 + 36x – 8y + 4 = 0

collect the x and y terms together

=> 9(x^2 + 4x) + 4(y^2 – 2y) = -4

complete the squares of the terms within brackets

=> 9( x^2 + 4x + 4) + 4(y^2 – 2y + 1) = -4 + 36 + 4

=> 9(x + 2) ^2 + 4(y – 1) ^2 = 36

divide by 36

=> (x + 2)^2 / 4 + (y – 1)^2 / 9 = 1

This is of the form (x – h)^2/ b^2 + ( y – k)^2/a^2 = 1

The center is given by (h, k ) = ( -2 , 1)

The vertices are (h , k + a) and (h, k – a) or ( -2 , 4) and (-2, -2)

The foci are (h, k + sqrt( a^2 – b^2)) and (h, k - sqrt( a^2 – b^2)) or ( -2 , 1 + sqrt 5) and ( -2, 1 – sqrt 5)

**The required center is (-2, 1). The vertices are ( -2 , 4) and (-2, -2) and the foci are ( -2 , 1 + sqrt 5) and ( -2, 1 – sqrt 5)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now